Disorder Dynamics in Battery Nanoparticles During Phase Transitions Revealed by Operando Single‐Particle Diffraction (Adv. Energy Mater. 12/2022). Issue 12 (24th March 2022) - Huang, Jason J.; Weinstock, Daniel; Hirsh, Hayley; Bouck, Ryan; Zhang, Minghao; Gorobtsov, Oleg Yu.; Okamura, Malia; Harder, Ross; Cha, Wonsuk; Ruff, Jacob P. C.; Meng, Y. Shirley; Singer, Andrej
Abstract : Sodium‐Ion Batteries In article number 2103521, Jason J. Huang and co‐workers use operando single particle X‐ray diffraction to probe disorder dynamics in individual cathode particles of Nax[Ni1/3 Mn2/3 ]O2, an archetypal cathode material for sodium‐ion batteries. The high throughput technique reveals the role of order‐disorder transitions in the detrimental P2‐O2 structural phase transition. These findings serve to guide the design of sodium‐ion battery cathodes with a longer cycle life.